Endocrine Regulation of Metabolism: Hormonal Control and Feedback Systems - Vladimirovna, Sarkisova Victoria; Norbekovich, Toshmamatov Baxtiyor (American Journal of Biology and Natural Sciences, 2025)
This article explores the fundamental mechanisms through which the endocrine system regulates human metabolism. It highlights the hormonal control pathways, feedback loops, and physiological responses that maintain metabolic homeostasis. Special emphasis is placed on major metabolic hormones, their sites of secretion, mechanisms of action, and the coordinated feedback systems that ensure balance in energy production, storage, and utilization. This scientific work examines how endocrine mechanisms direct metabolic functions through hormone-driven regulation and precisely coordinated feedback loops. The focus is placed on the interaction of major metabolic hormones, the modulation of biochemical pathways, and the stability provided by negative feedback systems. The text also analyzes how these regulatory structures adapt to physiological changes such as feeding, fasting, stress, and variations in energy demand. By integrating data from experimental and clinical sources, the article presents a detailed explanation of the dynamic hormonal network that sustains metabolic equilibrium.